Energy Metabolism on Mitochondrial Maturation and Its Effects on Cardiomyocyte Cell Fate - Persad, Kaya L.; Lopaschuk, Gary D. (Frontiers in Cell and Developmental Biology, 2022)
Alterations in energy metabolism plays a major role in the lineage of cardiomyocytes, such as the dramatic changes that occur in the transition from neonate to newborn. As cardiomyocytes mature, they shift from a primarily glycolytic state to a mitochondrial oxidative metabolic state. Metabolic intermediates and metabolites may have epigenetic and transcriptional roles in controlling cell fate by increasing mitochondrial biogenesis. In the maturing cardiomyocyte, such as in the postnatal heart, fatty acid oxidation increases in conjunction with increased mitochondrial biogenesis driven by the transcriptional coregulator PGC1-α. PGC1-α is necessary for mitochondrial biogenesis in the heart at birth, with deficiencies leading to postnatal cardiomyopathy. While stem cell therapy as a treatment for heart failure requires further investigation, studies suggest that adult stem cells may secrete cardioprotective factors which may regulate cardiomyocyte differentiation and survival. This review will discuss how metabolism influences mitochondrial biogenesis and how mitochondrial biogenesis influences cell fate, particularly in the context of the developing cardiomyocyte. The implications of energy metabolism on stem cell differentiation into cardiomyocytes, and how this may be utilized as a therapy against heart failure and cardiovascular disease will also be discussed.